2020
DOI: 10.1016/j.sleh.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The association of goal-striving stress with sleep duration and sleep quality among African Americans in the Jackson Heart Study

Abstract: Background: African Americans (AAs) report a higher frequency of certain stressors over their lifetime which may impact biological processes that can impair sleep. For this reason, goalstriving stress (GSS), the difference between aspiration and achievement, weighted by disappointment, may contribute to poor sleep quality and suboptimal sleep duration among AAs. Methods:We completed a cross-sectional analysis using exam 1 data (2000)(2001)(2002)(2003)(2004) from the Jackson Heart Study (JHS) (n=4943). GSS was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Studies examining work-related stress among essential and frontline workers, more broadly and during the COVID-19 pandemic have linked these conditions to greater sleep disturbance and poorer sleep quality ( El-Hage et al, 2020 ; McKibbin & Fernando, 2020 ). Research has indicated that sleep problems can co-occur with other mental health-related disorders ( Cain-Shields et al, 2020 ; Williams, 2008 ). Further, work conditions may contribute to overall health and life expectancy ( Goh et al, 2015 ; Lee et al, 2019 ; Okechukwu et al, 2014 ).…”
mentioning
confidence: 99%
“…Studies examining work-related stress among essential and frontline workers, more broadly and during the COVID-19 pandemic have linked these conditions to greater sleep disturbance and poorer sleep quality ( El-Hage et al, 2020 ; McKibbin & Fernando, 2020 ). Research has indicated that sleep problems can co-occur with other mental health-related disorders ( Cain-Shields et al, 2020 ; Williams, 2008 ). Further, work conditions may contribute to overall health and life expectancy ( Goh et al, 2015 ; Lee et al, 2019 ; Okechukwu et al, 2014 ).…”
mentioning
confidence: 99%
“…Importantly, this special issue contains examples of such critical work, including research investigating clinical, behavioral, and community-related correlates of sleep duration and efficiency among middle-aged Black/African American smokers 32 ; an examination of the link between sleep and physical activity for work and leisure among a sample of Latinx adults in the U.S. 33 ; and the link between goal-striving stress and sleep (duration and quality) among a sample of African American men and women from the Jackson Heart Study. 34 …”
Section: Key Contributions Of the Virtual Special Issuementioning
confidence: 99%
“…Most of the studies in this special issue focus on disparities in sleep duration 30 , 31 , 33 , 35 or a combination of sleep duration and sleep quality. 26 , 27 , 32 , 34 , 40 The most prevalent approach has been the use of subjective assessments of sleep duration and sleep quality, with two studies employing the use of actigraphy to objectively measure sleep duration, sleep efficiency, and wake time after sleep onset. 27 , 32 It will be necessary for future research to extend the scope of sleep health disparities by incorporating comprehensive assessments of sleep across a range of sleep health facets: abnormalities in sleep stages, sleep onset latency, daytime sleepiness, time in bed, night awakenings, inconsistencies in bedtimes and wake times, as well as a various sleep and circadian rhythm disorders.…”
Section: Key Contributions Of the Virtual Special Issuementioning
confidence: 99%
“…The manuscript ‘ The Association between Goal-Striving Stress and Rapid Kidney Function Decline among African Americans: The Jackson Heart Study ’ 5 published in this issue of Journal of Investigative Medicine aims to address the fact that traditional risk factors do not fully explain the disproportionate risk of ESRD in African Americans. In this study, the authors explore the association between rapid kidney function decline (RKFD) with a non-traditional risk factor, goal-striving stress (GSS), in African Americans with preserved eGFR and no proteinuria at baseline.…”
mentioning
confidence: 99%